1985
DOI: 10.1128/mcb.5.8.1859
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an activatable promoter: sequences in the simian virus 40 late promoter required for T-antigen-mediated trans activation.

Abstract: The late promoter of simian virus 40 (SV40) is activated in trans by the viral early gene product, T antigen. We inserted the wild-type late-promoter region, and deletion mutants of it, into chloramphenicol acetyltransferase transient expression vectors to identify promoter sequences which are active in the presence of T antigen. We defined two promoter activities. One activity was mediated by a promoter element within simian virus 40 nucleotides 200 to 270. The activity of this element was detectable only in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
138
0
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 67 publications
3
138
0
1
Order By: Relevance
“…Alternatively, in pRC4CATori the cytochrome c promoter is positioned 2.5 kilobases downstream from the late side of the SV40 origin, and T antigen may trans-activate this promoter, as it does the SV40 late genes, through specific origin sites (5,6,18,19). To distinguish between these T-antigendependent activities, a replication-defective origin, identical to that in pRC4CATori except for a 4-bp deletion in Tantigen-binding site 11 (12), was used for the construction of pRC4CAToriA, a replication-defective derivative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, in pRC4CATori the cytochrome c promoter is positioned 2.5 kilobases downstream from the late side of the SV40 origin, and T antigen may trans-activate this promoter, as it does the SV40 late genes, through specific origin sites (5,6,18,19). To distinguish between these T-antigendependent activities, a replication-defective origin, identical to that in pRC4CATori except for a 4-bp deletion in Tantigen-binding site 11 (12), was used for the construction of pRC4CAToriA, a replication-defective derivative.…”
Section: Resultsmentioning
confidence: 99%
“…It is unlikely that T antigen itself augments these cellular promoters by direct binding, because the pure protein did not bind to the cytochrome c promoter under conditions in which the interaction of T antigen with known binding sites in the SV40 origin was clearly detected. Likewise, activation of the SV40 late genes by T antigen can occur in the absence of T-antigen-binding sites (19). Recently, the transcription factor that mediates the zinc-dependent induction of the human metallothionein II promoter has been shown to be required for maximal activity of the SV40 enhancer (37).…”
Section: Discussionmentioning
confidence: 99%
“…The plasmid that served as a template for the RNA probe for RNase protection assays, named pGEM2-PAS, was constructed by isolating the SV40 polyadenylation signal- The plasmid used as a source of T antigen in cotransfection experiments was p6-ldL, described elsewhere (25).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have suggested that in the absence of DNA replication, T antigen also plays a significant role, both direct and indirect, in activating late transcription (10)(11)(12)(13).…”
mentioning
confidence: 99%